Processable Rylene Diimide Dyes up to 4 nm in Length: Synthesis and STM Visualization. Issue 36 (16th August 2013) - Yuan, Zhongyi; Lee, Shern‐Long; Chen, Long; Li, Chen; Mali, Kunal S.; De Feyter, Steven; Müllen, Klaus
<x xml:space="preserve">Abstract</x> Long and planar: Facile syntheses of soluble hexarylene diimides (HDI) and octarylene diimides (ODI) are described (see figure). They are stable in both solution and the solid state and exhibit broad and intense NIR absorption. Scanning tunneling microscopy (STM) reveals that HDI, after deposition from solution, forms a unique herringbone bilayer or stable multilayers depending on the concentration.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>